P291 Long term outcomes of children with ulcerative colitis after acute severe colitis: a multicenter study from the GETAID pédiatrique group. (30th January 2023) - Pigneur, B; Cochet, M; Delphine, L; Coopman, S; Raphael, E; Thierry, L; Claire, D; Stéphanie, W; Rémi, D L; Georges, D; Valérie, B; Anne, B; et al.
Abstract: Background: Acute Severe Colitis (ASC) is a frequent and severe complication of ulcerative colitis (UC) that can occur at any time during the disease. Its prognosis can be severe with a high risk of colectomy. The use of immunosuppressants and more recently biotherapies seem to reduce the risk of colectomy. We wished to study the long-term evolution of paediatric-onset UC patients after ASC. Methods: This retrospective study was conducted in 12 centres of the GETAID paediatric in France. Data on patients with UC aged < 18 years admitted with ASC (defined as paediatric ulcerative colitis activity index [PUCAI] score ≥ 65) between January 2010 and January 2021 were collected at discharge and at 1, 3 and 5 years after admission. The primary outcome of our study was colectomy-free rates at one year. A univariate analysis comparing the profile at diagnosis and at ASC of patients who underwent colectomy, and others was performed to look for prognostic factors associated with the risk of surgery. Results: Of the 102 patients admitted with ASC, 95 [93%] were treated with corticosteroids. Forty-six [48%] patients were escalated to second-line therapy, mainly to infliximab. Nine patients [8.8%] underwent colectomy before discharge. Long-term follow-up showed colectomy-free rates were 83%, 76% and 72% at 1, 3 and 5 years after initial ASC admission, respectively. In a multivariate analysis, active disease, and use of methotrexate were significantly associated with a higher risk of colectomy. A short delay between diagnosis and ASC, rapid steroid use for ASC and second line therapy with azathioprine and Infliximab were significantly associated with a lower risk of colectomy. Conclusion: The rate of colostomy remains high after an episode of acute colitis despite the earlier use of biotherapies. But long-term outcome of paediatric-onset UC patients is good with sustained clinical and biological remission.